(untitled) (Discourse of Law and Administration, 2023)
The subject of the study is the analysis of the resolution of the Supreme Court of May 17, 2018, III CZP 11/18, in which the court found that „the parents of an adult child who is completely incapacitated due to mental disability and for whom a guardian has been appointed are not entitled to demand decision by the guardianship court on how to maintain contact with this child. The author shared the Supreme Court’s position, pointing out the arguments supporting its accuracy